Price Determinants of Bitcoin as An Investment in the Philippine Context - Adriano, Christian Alexander; Kadomura, Marie; Villar, John Alfred; Rosete, Marie Antoinette (International Journal of Social and Management Studies, 2022)
Bitcoin is an open-sourced, decentralized system, despite its intangible characteristic, it is the most prominent digital currency developed by an unknown programmer famously known as Nakamoto in 2008. The aim of this paper is to render evidence whether Bitcoin is a secured platform for investing despite its volatile behavior by verifying whether the Market Capitalization, Trade Volume, Exchange Rate (USD) are critical determinants of Bitcoin price. The research makes use of secondary data from coindesk.com to gather results using Multiple Linear Regression and the Ordinary Least Squares in analyzing the relationship between the variables. Market Capitalization fails to reject the null hypothesis. Trade Volume and Exchange Rate (USD) are variations that can explain 93.87% of Bitcoin price. The results gathered shows that Bitcoin prices are highly volatile because of the volatility of the Independent Variables. Bitcoin as a means of investment is not a viable option of investment for its sudden volatility of high-high risk with a high-high return or loss.